Distribuiç\~ao de renda, transferências federais e imigraç\~ao: Um estudo de dados em painel para as Unidades da Federaç\~ao do Brasil - Adolfo Sachsida; Marcelo Abi-Ramia Caetano; Pedro Albuquerque (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This article verifies the impact of both federal transfers to states and income inequality over imigration. The innovation here is the use of aggregate data to verify the impact of public policy over migration. The econometric results suggest a positive effect of federal transfers to states over imigration. That is, an increase in the cash transferences from Federal government to states increases migration to those states. Besides that, we found that high income inequality in a state decreases migration to that state. Moreover, the results vary according to the group division of Brazilian states, indicating a scale effect.
Keywords: R23; C23; 330; Finanzausgleich; Binnenwanderung; Brasilien